Pengaruh Kesadaran Wajib Pajak dan Sanksi Pajak Terhadap Kepatuhan dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Medan Helvetia - Nainggolan, Amanda Anggriani; Yusnaini, Yusnaini; Sutanto, Hermawan (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of taxpayer awareness and tax sanctions on compliance in paying Land and Building Tax (PBB) in Medan Helvetia District. This research employs a quantitative approach with data collected through questionnaires distributed to 100 taxpayer respondents. The sample was determined using the Slovin formula. Descriptive data analysis was carried out using SPSS 25, while the structural model testing was conducted using SmartPLS 4.0. The results of the study show that, partially, taxpayer awareness does not have a significant effect on compliance in paying Land and Building Tax (PBB), whereas tax sanctions have a significant effect. Simultaneously, taxpayer awareness and tax sanctions have a significant effect on tax compliance. These findings indicate that strict sanctions are more effective in encouraging taxpayer compliance than increasing awareness alone.